WAP PKI and certification path validation. (9th February 2007) - Satizabal, Cristina; Paez, Rafael; Forne, Jordi
The fast evolution of mobile communications and their convergence with internet make necessary to adapt the security services to this new environment. WPKI (Wireless Application Protocol Public Key Infrastructure) can provide these services, but the features of the mobile devices make it a difficult task, especially for complex processes such as the certification path validation that requires long time and resources. In this paper, we show the limitations of WPKI from the verifier's point of view and determine the computational cost and storage capacity required by a verifier, with a mobile terminal, to carry out a certification path validation process when different revocation mechanisms are used.